Influence of malonic acid and manganese dioxide on humic substance formation and inhibition of CO2 release during composting. (December 2020) - Zhang, Shuang; Wei, Zimin; Zhao, Meiyang; Chen, Xiaomeng; Wu, Junqiu; Kang, Kejia; Wu, Yunying
Graphical abstract: Highlights: Malonic acid inhibits CO2 release by affecting the tricarboxylic acid cycle. MnO2 acts through biological and non-biological pathways. Malonic acid, MnO2, malonic acid + MnO2 can promote the formation of HA. Malonic acid and MnO2 can change bacterial community structure during composting. Abstract: The aim of this study was to explore the effects of malonic acid (MA), manganese dioxide (MnO2 ), malonic acid combined with manganese dioxide (MA + MnO2 ) addition on reducing CO2 emission and promoting humic substance (HS) formation during composting. The result showed that the addition of MA and MnO2 were an efficient way to reduce CO2 emission. Meanwhile, the CO2 emissions in the MA + MnO2 treatment was 36.8% less than that of the CK, and the amount of humic acid (HA) produced in the MnO2 treatment was 38.7% higher than that of the CK. Structural equation models demonstrated that the addition of exogenous substance promoted the conversion of amino acids and reducing sugars to HA. The addition of exogenous substances was the main reason for influencing the concentration of HA. In general, this research provided theoretical supports for the addition of exogenous substances to promote HA formation during composting.